Dose effects of alfentanil in human analgesia - Hill, H; Walter, M H; Saeger, L; Sargur, M; Sizemore, W; Chapman, C R (Clinical pharmacology and therapeutics, 1986)
Alfentanil, a rapidly acting opioid, was given in subanesthetic doses to 10 subjects in a laboratory setting. Analgesia was assessed from the subjects' responses to painful dental stimulation. A subjective pain report (PR) and brain evoked potential (EP) amplitude were obtained repeatedly before and after injection on each of 4 testing days, on which the following intravenous doses were administered: 0 (saline solution), 5, 10, and 15 micrograms/kg. Significant dose effects were observed for EP amplitude during but not beyond the distributional t1/2 of the drug, but significant effects on the PR extended beyond this time point. Mean volume of distribution, total body clearance, and distribution t1/2 did not differ significantly across the doses of alfentanil. Strong correlations between each effect measure and plasma drug concentration were observed at all doses and were significant at P less than 0.01. The EP scores tracked the distribution of alfentanil very closely, but the correlation between EP amplitude and plasma alfentanil concentration was lower during the elimination phase. In contrast, the PR effects closely tracked the elimination of alfentanil but not its distribution. These findings suggest that EP amplitude and the PR represent two different central effects in opioid analgesia.